Indicators of mineral metabolism and dental status of young rats born from female with methionine-induced hyperhomocysteinemia - Kutelmakh, O.; Lesyk, R.; Chumakova, Yu.; Bondar, S.; Dronenko, V.; Shkilniak, L. (My University, 2021)
We assume that the violation of homocysteine (Hcy) metabolism and vitamin D level in mothers’ utero causes various abnormalities in offspring, including hard-woven teeth and periodontium impairments. The aim of this study was to evaluate the biochemical parameters of blood and alveolar bone homogenates and assess dental status of offspring born from female rats under long-term methionine hyperhomocysteinemia (HHcy). Clinical, biochemical and morphometric studies were performed on 30 female rats and 281 infantile and early juvenile rats. Serum Hcy levels were determined by competitive immunoassay with electrochemiluminescent detection, 25-hydroxyvitamin D (25OHD ) level was estimated by EL ISA. No violation of Hcyserum level was found in rats born from females with long-term methionine-induced hyperhomocysteinaemia. Hyperhomocysteinaemic diet caused by long-term use of methionine reduced the level of total and ionized calcium and phosphates in the blood of pregnant females and their offspring. Elevated levels of homocysteine and decreased vitamin D levels in pregnant females caused a delay in the complete physiological eruption of permanent molars in their offspring. Biochemical changes in the blood, jawbones and the presence of early carious processes in the teeth of young rats, in our opinion, are the result of metabolic disorders in utero caused by hyperhomocysteinaemia and vitamin D deficiency in their mothers.
Kutelmakh O. Indicators of mineral metabolism and dental status of young rats born from female with methionine-induced hyperhomocysteinemia / O. Kutelmakh, R. Lesyk, Yu. Chumakova, S. Bondar, V. Dronenko, L. Shkilniak // Ukr. Biochem. J. - 2021. – Vol. 93, № 6. – P. 93-100.
Keywords: methionine-induced hyperhomocysteinaemia; homocysteine; vitamin D; choline; dental status; tooth eruption